2009
DOI: 10.1088/0741-3335/51/8/085006
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency magnetohydrodynamics and geodesic acoustic modes in toroidally rotating tokamak plasmas

Abstract: This paper analyses low-frequency magnetohydrodynamic (MHD) modes, especially the geodesic acoustic modes (GAMs), in toroidal plasmas with large aspect ratio and circular cross section, including the effects of toroidal plasma rotation. A system of equations describing MHD modes with frequency of the order of the sound frequency in such plasmas is derived from the Frieman-Rotenberg equation, using a technique where the plasma perturbation ξ and the perturbed magnetic field Q are expanded separately in the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
115
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(127 citation statements)
references
References 44 publications
11
115
1
Order By: Relevance
“…While standard gyrokinetic models struggle with these features, the MHD results of Ref. [5] appear to agree with experimental measurements of GAMs using magnetic probes. Also, perhaps little known is the effect that equilibrium toroidal plasma rotation (e.g.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…While standard gyrokinetic models struggle with these features, the MHD results of Ref. [5] appear to agree with experimental measurements of GAMs using magnetic probes. Also, perhaps little known is the effect that equilibrium toroidal plasma rotation (e.g.…”
Section: Introductionsupporting
confidence: 60%
“…In Section III where static (non-rotating) plasmas are considered, it will be shown that zonal modes are exactly electrostatic, and there are no flows across magnetic flux surfaces. While full electromagnetic calculations have been made for GAMs and zonal modes [5], analysis of the continuum mode frequencies in rotating plasma are recovered on setting ξ ψ p = ξ p · ∇ψ = 0 and δB = 0 in Eq. (13).…”
Section: B Gams and Zonal Flows In Isothermal Ideal Mhd Rotating Plamentioning
confidence: 99%
See 1 more Smart Citation
“…In integrated form the effect first appeared in an analysis of the internal kink mode [5] where it was grouped with inertial terms and was denoted as "flutter." The effect also surfaced in more recent analyses [6,7]. In Ref.…”
Section: Introductionmentioning
confidence: 65%
“…A large piece of the Comment is devoted to the proposition to go out of use in MHD the conventional sonic Mach number used in II and in a lot of papers by the other authors (see, e.g., Refs. [4][5][6][7]. Although this subject is rather general and has no specific relation to the commented paper II, there is a sense to note the following.…”
mentioning
confidence: 99%